Enhancing Elementary School Students' Cognitive Understanding of Indonesian Language Through Problem-Based Learning Model Assisted by Interactive Power Point Media - Swari, Luh Gede Mirah Indra; Kristiantari, Maria Goreti Rini; Werang, Basilius Redan (Universitas Pendidikan Ganesha, 2024)
The low learning outcomes of elementary school students in Indonesian language subjects remain a persistent issue, primarily due to the continued use of conventional teaching methods that emphasize rote learning and teacher-centered instruction. This approach limits students' active participation, inhibits critical thinking development, and reduces their motivation for independent learning. To address this challenge, this study investigates the effectiveness of the problem-based learning (PBL) model assisted by interactive PowerPoint media in enhancing students’ cognitive understanding. This study employs a quasi-experimental design with a Nonequivalent Pretest-Posttest Control Group Design. The sample consists of 55 fifth-grade students, divided into an experimental group taught using PBL assisted by interactive PowerPoint media and a control group taught using conventional methods. Data were collected using multiple-choice objective tests and analyzed through descriptive statistics and t-tests to compare learning outcomes between the two groups. The results reveal a statistically significant improvement in students' cognitive knowledge competence in the experimental group compared to the control group. These findings demonstrate that integrating PBL with interactive power point media is an effective strategy to enhance students’ cognitive understanding and learning motivation. The study underscores the importance of adopting innovative and student-centered teaching models to improve cognitive learning outcomes in Indonesian language education at the elementary level.